2011
DOI: 10.2176/nmc.51.415
|View full text |Cite
|
Sign up to set email alerts
|

Radiological Predictive Factors for Regrowth of Residual Benign Meningiomas

Abstract: The pre-and postoperative radiological predictive factors for the regrowth of residual benign meningiomas were investigated in 80 of 327 patients who underwent first surgery for intracranial meningioma, who met the following conditions: residual tumor observed on postoperative imaging, follow up for more than 5 years or until regrowth of the residual tumor, histological diagnosis of World Health Organization grade I, and no additional therapy performed within 1 month after surgery. These 80 patients were divid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 38 publications
(76 reference statements)
1
5
0
Order By: Relevance
“…Consistent with the findings in the previous smaller series, tumor volume [ 2 , 4 , 11 , 21 ], disruption of the arachnoid layer [ 4 , 11 , 21 ], and an irregular tumor shape [ 11 , 15 , 16 , 21 ] were associated with an increased risk of recurrence , while heterogeneous contrast enhancement was mostly not correlated with prognosis [ 10 , 15 , 16 ]. However, odds ratio of the tumor volume and the sensitivity and specificity were found to be low, indicating its limited value for predicting tumor recurrence.…”
Section: Discussionsupporting
confidence: 87%
“…Consistent with the findings in the previous smaller series, tumor volume [ 2 , 4 , 11 , 21 ], disruption of the arachnoid layer [ 4 , 11 , 21 ], and an irregular tumor shape [ 11 , 15 , 16 , 21 ] were associated with an increased risk of recurrence , while heterogeneous contrast enhancement was mostly not correlated with prognosis [ 10 , 15 , 16 ]. However, odds ratio of the tumor volume and the sensitivity and specificity were found to be low, indicating its limited value for predicting tumor recurrence.…”
Section: Discussionsupporting
confidence: 87%
“…Our results indicated significant differences in tumor shape and volume between the recurrent and non-recurrent groups. Similarly, several researchers found that irregular tumor shape and larger tumor volumes were associated with greater proliferative potential, and active proliferation leads to increased recurrence after resection ( 4 , 6 , 15 17 ). In addition, we demonstrated that peritumoral brain edema (PTBE), including peritumoral edema volume and peritumoral edema index, was strongly associated with prognosis.…”
Section: Discussionmentioning
confidence: 92%
“…Although grade II/III meningiomas have more aggressive biological behavior and might exhibit faster recurrence, there are also some high grade meningiomas that biologically behave more like benign lesions by our observation ( Figure 7 ). Likewise, many studies showed that it was inadequate to predict postoperative recurrence and develop individualized treatment strategies based solely on WHO classification ( 3 , 6 , 8 , 9 , 11 13 , 17 ). Consequently, in this study, we established a prediction model integrating clinical data, imaging, and pathology for tumor prognosis, and explored and developed personalized treatment strategies base on this model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Shakir et al 35 showed that local control is strongly correlated with the postoperative tumor volume prior to adjuvant radiation in a series of 70 atypical meningiomas and delineated a critical cutoff value of approximately 9 cm 3 . Fujimoto et al, 38 however, outlined residual tumor volume of ≥ 3 cm 3 as a predictor of progression in uni-and multivariate analysis. In contrast, our group could not determine a prognostic impact of the postoperative tumor volume in 49 subtotally (Simpson grade ≥ IV) resected skull base meningiomas in a previous study.…”
Section: Prognostic Value Of the Postoperative Tumor Volume Compared To Intraoperatively Assessed Eormentioning
confidence: 99%